Konsep Pemberdayaan Masyarakat Dalam Pandangan Karl Marx dan Max Weber - Derry Ahmad Rizal; Moh. Syaiful Bahri (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Community empowerment is a social movement that aims to make changes towards better things. This covers the economic side, development and people's lives are more organized. This practice in community empowerment requires a process and takes time. The role of the government as a policy is certainly a supporter in doing empowerment, the community as the main role in this activity. In this article aims to discuss the concept of community empowerment in outline, but especially presenting the concept of previous thinkers. Tokoh filusuf who has the concept of sociological thinkers or intersects with community empowerment. The figures presented in this paper are Karl Marx and Max Weber, the form of thought or perspective of these two figures in social science or sociology. In this paper using qualitative descriptive metode with a library or literature study approach. Presenting the concept of the thoughts of the two figures, along with their work and thoughts. Strengthening this concept of thinking also presents case studies in the application of community empowerment.